Phase transition of BiMnO3 multiferroic thin film by Landau-Ginzburg theory - Alrub, A.M.; Ong, L.H.; Chew, Khian Hooi; Khoshman, J.M.; Al Shabaan, G.N.; Hilaleh, R.A. (World Scientific Publishing, 2016)
Magnetoelectric (ME) multiferroic bismuth manganite (BiMnO3) has ferroelectric (FE) and ferromagnetic order parameters that coupled biquadratically. Landau free energy expression in these order parameters is proposed to investigate the phase transition and thermodynamic properties of a BiMnO3 film. The surface energy term is included in the free energy. We find that the ME coupling enhances the magnetic transition temperature. The magnetization and polarization order parameters are both increased strongly below the new magnetic transition temperature. The curves for magnetization and polarization versus temperature show that the phase transition is second-order. The entropy, free energy, and specific heat of the BiMnO3 multiferroic are calculated. Thickness-driven phase transitions for magnetization and polarization of BiMnO3 thin film are clearly indicated.